The role of LIN28 in the molecular regulation of placenta development and function - Seabrook, Jill L., author; Winger, Quinton A., advisor; Clay, Colin M., committee member; Bouma, Gerrit J., committee member; DeLuca, Jennifer G., committee member (Colorado State University. Libraries, 2013)
To view the abstract, please see the full text of the document.
Keywords: LIN28; trophoblast; syncytiotrophoblast; placenta